Gene Silencing: The Mechanism to Down Regulate the Target Gene - Shreya; Pandey, Ajeet Kumar; Bhandari, H. R. (International Journal of Bio-resource and Stress Management, 2018)
Gene silencing is one of the most efficient and promising functional genomics tools which down regulates the expression of a gene in a very precise manner and has significant impact on crop improvement. Silencing of a target gene can be achieved at two levels; transcriptional and post- transcriptional stages. In broader sense, transcriptional gene silencing occurs through the repression of the process of transcription while the post transcriptional gene silencing can occur through the degradation of the mRNA. Small RNA molecules like siRNAs & miRNAs are key players which mediate the mechanism of gene silencing. These small RNA molecules are generated through Dicer digestion of the endogenous or exogenous dsRNA by which RISC (RNA induced gene silencing complex) is activated which inhibits expression of a gene. Apart from these small RNA molecules, viruses can also accomplish gene silencing which is known as VIGS (Virus induced gene silencing). VIGS consists of cloning and inserting plant endogenous gene sequences in recombinant viral vectors, which are then inoculated in plants, triggering RNA interference. Gene silencing as reverse genetic tool, has been exploited successfully to build up the resistant against biotic (insect/pest, nematodes, viruses etc.) and abiotic stresses (drought, salinity, frost etc.), and for the enhancement of yield and quality parameters. With the development of cutting edge biotechnological tools and techniques, it is now affordable to knock down/down regulate the expression of any undesirable gene. Ultimately this kind of technology can be important to global food security and sustainability.